Epilepsy Transition in Ambulatory Care: Experiences and Benefits of an Epilepsy Transition Team - Patel, Amisha; Jan, Sophia; Steinway, Caren; Bullock, Alexandra; Greenberg, Adam; Thomas, Bethany; Fried, Lawrence E.; Brown, Lawrence; DiGiovine, Marissa (Journal of Pediatric Epilepsy, 2020)
Epilepsy is the fourth most common neurological disorder and affects people of all ages; however, at least 40% of children will continue to have seizures into adulthood. Children and youth with epilepsy (CYE) experience neurologic and extraneurologic changes that can negatively impact self-management skills necessary for optimal adult function. Those with intellectual disability have additional transition challenges. Improving the medical transition process for all CYE is vital and necessary. In this article, we will review some of the biologic, behavioral, psychologic, therapeutic, and social considerations for CYE complicating transition. We will then describe general approaches to transitioning CYE to adult care, specifically methods involving creating a framework with overarching transition aims in place, and share our experience at the Children's Hospital of Philadelphia implementing these approaches. Our comprehensive model for a formal transition policy, team structure, and ongoing assessment supporting CYE transitioning into adult care is a practical program that can be integrated into clinical care. Proper investment in the transition process will translate into measurable, significant long-term benefits for all involved.
Keywords: children and youth with epilepsy; transition; epilepsy